(untitled) (Revista Brasileira Multidisciplinar, 2008)
Objective: the objective was to compare the efficacy of individual treatment (consulting) and group treatment combined with individualized care, in childhood and juvenile obesity situations. Methodology: The study was carried out in 2 different places: in the Nutrition Clinic of the Integrated Health Clinic of UNIARA and in another clinical school. In both places there was a treatment with individual consultations, however, in the Integrated Health Clinic of UNIARA treatment was also done in group care. The target individuals were composed of children and adolescents of both sexes who participated in the consultations, however, only patients who were above the 85th percentile for BMI, according to the international reference population (NCHS, 2000), were included in the sample which was composed of 58 individuals. The choice of clinical records occurred at random in both places. Results: the most effective program in the positive change in dietary habits was group together with individual treatment, where 20 patients (68.96%) showed some change in eating behavior. In individual treatment, 11 patients (37.93%) showed some change in dietary habits existing before treatment. There was a reduction in the rate of obesity of 24% for patients in groups, however, both types of treatment were favorable to changes in dietary habits and weight reduction. The findings showed that the strategy of individualized care together with group care is an alternative for the treatment of overweight.